HUBUNGAN PENGETAHUAN TENTANG MAKANAN JAJANAN TERHADAP STATUS GIZI SISWA SEKOLAH DASAR INPRES BORONG JAMBU I KOTA MAKASSAR - fatmawaty fatmawaty; Adriyani Adam; Sukmawati Sukmawati; Sitti Saharia Rowa; Sri Wahyuni (Media Gizi Pangan, 2023)
Nutritional knowledge about the selection of good snack foods affects the intake of snack foods for school children, the final result of food intake will affect nutritional status. This study aims to determine the relationship of knowledge about street food to the nutritional status of Inpres Borong Jambu I Elementary School students, Makassar City. This research is an analytical research with a cross sectional study design. The samples were elementary school students in grades III, IV, V, and VI, totaling 82 students. Knowledge about street food was collected by filling out a questionnaire. Nutritional status is known through anthropometric measurements, namely height for age and then processed using the WHO Antro application. To find out the relationship between knowledge about street food and nutritional status, a Chi-Square statistical test was carried out using the SPSS program. Data is presented in the form of frequency distribution tables and narratives. The results showed that elementary school students' knowledge of snack foods was generally good, namely 93.9%, and normal nutritional status, namely 78.0%. Statistical analysis revealed that there was no relationship between knowledge about snack foods and nutritional status with a value of p = 0.913 (p <0.05). It is suggested that in order to develop research related to the relationship between knowledge about snack food and the nutritional status of elementary school students, the school pays more attention to the snack food sold at school and parents pay more attention to children's food consumption.Keywords : Knowledge, Nutritional status, Snacks.